The potential of melatonin in sepsis-associated acute kidney injury: Mitochondrial protection and cGAS-STING signaling pathway - Yuchun Cao; Xiaofang He; Zeyuan Liu; Liying Miao; Bin Zhu (Heliyon)
Melatonin (Mel) is known for various biological function, such as antioxidant and anti-inflammatory capabilities, as well as its ability to modulate immune responses, which can protect mitochondria and improve the prognosis of sepsis-associated acute kidney injury (SA-AKI). However, there is a multitude of theories regarding how Mel exerts its immune-modulating functions, with no consensus reached as of yet. We propose the protective effects of Mel on mitochondria are closely related to the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling pathway in the immune-inflammatory response. We intraperitoneally injected H151 and Mel into SA-AKI mouse models to interfere the cGAS-STING signaling pathway. By comparing behavioral, pathological, and molecular biology results, we discovered that Mel could reduce cGAS-STING signaling pathway while greatly relieving kidney damage and function. In addition, Mel-treated mice showed a significant increase in autophagosome formations, which might be linked to the cGAS-STING signaling pathway. Our findings suggest that Mel protection on kidney injury in SA-AKI mice is partially attributed to the inhibition of the cGAS-STING signaling pathway.